2021
DOI: 10.46303/ressat.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Responses to Multi-Modal Emergency Remote Learning During COVID-19 in a South African Higher Institution

Abstract: COVID-19 pandemic forced several higher education institutions (HEI) to operate remotely. Emergency remote teaching, using synchronous and asynchronous instruction, was adopted by several HEIs. The experiences of students with remote teaching and learning in certain situations are not fully understood, thus need to be explored. This study explored the experiences of students with the emergency remote teaching and learning practices adopted at a selected HEI in South Africa. A cross-sectional and self-administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Loneliness. Eleven studies revealed that students felt lonely during ERTL (Abubakar et al, 2022;Al-Hashmi, 2021;Bawa, 2020;Chattaraj & Vijayaraghavan, 2021;Ensmann et al, 2021;Gelles et al, 2020;Gqokonqana et al, 2022;Iglesias-Pradas et al, 2021;Matarirano et al, 2021;Minichiello et al, 2022;Pillay et al, 2021).…”
Section: Personal Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Loneliness. Eleven studies revealed that students felt lonely during ERTL (Abubakar et al, 2022;Al-Hashmi, 2021;Bawa, 2020;Chattaraj & Vijayaraghavan, 2021;Ensmann et al, 2021;Gelles et al, 2020;Gqokonqana et al, 2022;Iglesias-Pradas et al, 2021;Matarirano et al, 2021;Minichiello et al, 2022;Pillay et al, 2021).…”
Section: Personal Issuesmentioning
confidence: 99%
“…Internet. Twenty-three studies revealed that the most frequently reported challenge faced by students was the unreliability of internet connection during ERTL (Abubakar et al, 2022;Al-Hashmi, 2021;Alvarez, 2020;Amir et al, 2020;Bamoallem & Altarteer, 2022;Baran & Alzoubi, 2020;Basri et al, 2022;Chattaraj & Vijayaraghavan, 2021;Dorsah, 2021;Edmond et al, 2020;Gqokonqana et al, 2022;Jili et al, 2021;Korkmaz & Toraman, 2021;Kovacˇevic´et al, 2021;Lengetti et al, 2021;Matarirano et al, 2021;Pillay et al, 2021;Rahiem, 2020aRahiem, , 2020bShim & Lee, 2020;Shin & Hickey, 2021;Sumardi & Nugrahani, 2021;Tulaskar & Turunen, 2022;Wilcox & Vignal, 2020). Three studies revealed that students could not afford internet data for online learning during ERTL (Edmond et al, 2020;Matarirano et al, 2021;Husni Rahiem, 2021).…”
Section: Technologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, Mikeska et al (2022) explored the use of simulated environments that enabled preservice teachers to practice how to teach in virtual classrooms with avatars in place of learners. The preservice teachers viewed the simulation tool as valuable in mitigating the challenges posed by the COVID-19 pandemic (De Klerk et al, 2021;Dube et al 2022;Makura, 2022;Matarirano et al, 2021;Moyo et al, 2022;Nel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is a new learning concept where material can be delivered in class and online. Blended learning is defined as combining the advantages of e-learning, face-to-face, and practice (Matarirano et al, 2021;Omodan & Diko, 2021;Tsakeni, 2021) . Abdullah (2018) stated that this form of learning combines media, models, theories, face-toface, and online methods.…”
Section: Introductionmentioning
confidence: 99%